Astronomía al Aire: Mass Media Convergence in Astronomy and Astrophysics - Núñez, Luis A.; Rago, Héctor (TECCIENCIA, 2016)
The experience of Astronomía al Aire (Astronomy on air) is described. It is an outreach initiative involving traditional mass media like radio broadcast, and new digital ones, such blog, microblogging and video channel. We present several very preliminary successful results of this unique experience helping to create new science informal education environments in Latin America.